Best n-Term Approximations in Spaces with Nonsymmetric Metric - Rukasov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We determine exact values of n-term approximations of q-ellipsoids in the spaces \(S_φ^p, μ\) .